Estimation of process capability based on continuous and attribute data - Runje, Biserka (Array, 2019)
In the paper, a process capability and process performance analyses for continuous and attribute data are conducted by using an industry example. The inner diameter of the bearing rings is analysed by applying the normal capability analysis for the continuous data and by applying the binomial capability analysis for the attribute data. In order to quantify the process performance and process capability for continuous and attribute data, the sigma level or the process sigma is calculated. This represents an alternative method to calculating process capability indices and process performance indices.